Search and classify topics in a corpus of text using the latent dirichlet allocation model - Orlando Iparraguirre-Villanueva; Fernando Sierra-Liñan; Jose Luis Herrera Salazar; Saul Beltozar-Clemente; Félix Pucuhuayla-Revatta; Joselyn Zapata-Paulini; Michael Cabanillas-Carbonell (Institute of Advanced Engineering and Science, 2023)
This work aims at discovering topics in a text corpus and classifying the most relevant terms for each of the discovered topics. The process was performed in four steps: first, document extraction and data processing; second, labeling and training of the data; third, labeling of the unseen data; and fourth, evaluation of the model performance. For processing, a total of 10,322